Phloretin ameliorates hepatic steatosis through regulation of lipogenesis and Sirt1/AMPK signaling in obese mice - Liou, Chian-Jiun (Cell Biosci, 2020)
BACKGROUND: Phloretin is isolated from apple trees and could increase lipolysis in 3T3-L1 adipocytes. Previous studies have found that phloretin could prevent obesity in mice. In this study, we investigated whether phloretin ameliorates non-alcoholic fatty liver disease (NAFLD) in high-fat diet (HFD)-induced obese mice, and evaluated the regulation of lipid metabolism in hepatocytes. METHODS: HepG2 cells were treated with 0.5 mM oleic acid to induce lipid accumulation, and then treated with phloretin to evaluate the molecular mechanism of lipogenesis. In another experiment, male C57BL/6 mice were fed normal diet or HFD (60% fat, w/w) for 16 weeks. After the fourth week, mice were treated with or without phloretin by intraperitoneal injection for 12 weeks. RESULTS: Phloretin significantly reduced excessive lipid accumulation and decreased sterol regulatory element-binding protein 1c, blocking the expression of fatty acid synthase in oleic acid-induced HepG2 cells. Phloretin increased Sirt1, and phosphorylation of AMP activated protein kinase to suppress acetyl-CoA carboxylase expression, reducing fatty acid synthesis in hepatocytes. Phloretin also reduced body weight and fat weight compared to untreated HFD-fed mice. Phloretin also reduced liver weight and liver lipid accumulation and improved hepatocyte steatosis in obese mice. In liver tissue from obese mice, phloretin suppressed transcription factors of lipogenesis and fatty acid synthase, and increased lipolysis and fatty acid β-oxidation. Furthermore, phloretin regulated serum leptin, adiponectin, triglyceride, low-density lipoprotein, and free fatty acid levels in obese mice. CONCLUSIONS: These findings suggest that phloretin improves hepatic steatosis by regulating lipogenesis and the Sirt-1/AMPK pathway in the liver.